PSPWM BASED SCML I TOPOLOGY WITH A REDUCED NUMBER OF SWITCHES FOR AC POWER DISTRIBUTION SYSTEM - KUMAR , DR. M.NAVEEN; MR. B.SREENU; MR. N.LAXMAN (The journal of contemporary issues in business and government, 2017)
The main aim of this project is Phase Shift Pulse Width Modulation (PSPWM) based Switched Capacitor Multi Level Inverter (SCMLI) topology with a reduced number of switches for AC power distribution system. The output voltage and current waveforms from the various PV sources are being produced by the power electronics converters. In recent years, PV applications have concentrated on the delivery of high-frequency AC electricity. With DC/AC SCMLIs, for example, the number of power conversion stages and components is greatly reduced resulting in an increased rate of conversion. A new PSPWM based SCMLI topology with fewer switches and a self-balanced floating capacitor (FC) voltage is proposed in this project. A single dc source and three dc sources make up the suggested topology. With the proposed design, a voltage output (Vo) that is twice as high as the input voltage can be generated (Vin). Compared to other topologies recently proposed, this one has a faster discharge time. In addition, the voltage stress on switches is les in relation to the load voltage. The proposed simulation results are studied in MATLAB/SIMULINK environment.